Creation of Minimum Standard Tool for Palliative Care in India and Self-evaluation of Palliative Care Programs Using It - Rajagopal, MR (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: It is important to ensure that minimum standards for palliative care based on available resources are clearly defined and achieved. AIMS: (1) Creation of minimum National Standards for Palliative Care for India. (2) Development of a tool for self-evaluation of palliative care organizations. (3) Evaluation of the tool in India. In 2006, Pallium India assembled a working group at the national level to develop minimum standards. The standards were to be evaluated by palliative care services in the country. MATERIALS AND METHODS: The working group prepared a “standards” document, which had two parts – the first composed of eight “essential” components and the second, 22 “desirable” components. The working group sent the document to 86 hospice and palliative care providers nationwide, requesting them to self-evaluate their palliative care services based on the standards document, on a modified Likert scale. RESULTS: Forty-nine (57%) palliative care organizations responded, and their self-evaluation of services based on the standards tool was analyzed. The majority of the palliative care providers met most of the standards identified as essential by the working group. A variable percentage of organizations had satisfied the desirable components of the standards. CONCLUSIONS: We demonstrated that the “standards tool” could be applied effectively in practice for self-evaluation of quality of palliative care services.